Biodiversity and impact of large hydroelectric projects in the Tocantins-Araguaia river basin district: a systemic analysis - Choueri, Ricardo Brasil; Azevedo, Josué Anderson Rêgo (Sociedade & Natureza, 2018)
Hydroelectric power plants are among the infrastructure projects that cause large impacts on biodiversity. Much has been discussed about the different ways to mitigate or compensating these impacts and the Systematic Conservation Planning (PSC) can be an important tool to address these impacts in an integrated manner and on a regional scale. This study aims to analyze and quantify the impact of large hydroelectric projects in the Araguaia-Tocantins Hydrographic Region. We used endangered and endemic species of vertebrates as indicator groups for conservation priorities, in order to propose subsidies for systemic territorial planning and conservation. We considered two scenarios, one with only the hydroelectric plants in operation (8 plants) and another including all the planned hydroelectric plants (26 plants). Forty-two species were selected as conservation targets (surrogates), including endemic and endangered species of vertebrates. We selected conservations goals for each surrogate, in three levels according to the size of geographical distribution of each surrogate. For the prioritization process, we used the ConsNet software. The results indicate that, considering the current scenario, it would be necessary to increase 6.1 million ha in UC of Integral Protection, or 450% of the current area in the river basin district, and the future scenario indicates an increase of almost 100,000 ha to that value. The work also indicates that the PSC can be a powerful tool in the search for consensus among actors with different interests in the basins.